Chronic Odontogenic Rhinosinusitis: Optimization of Surgical Treatment Indications. Issue 6 (November 2020) - Simuntis, Regimantas; Kubilius, Ričardas; Tušas, Paulius; Leketas, Marijus; Vaitkus, Justinas; Vaitkus, Saulius
Background: The treatment of chronic odontogenic and nonodontogenic rhinosinusitis is different. It requires the elimination of odontogenic cause and optimal sinus surgical treatment. To date, there are no clear indications when sinus surgical treatment is necessary. Objective: Our aim was to define clear indication(s) for sinus surgical treatment in patients with chronic odontogenic rhinosinusitis after elimination of odontogenic cause. Methods: A group of 96 patients with chronic odontogenic rhinosinusitis caused by apical periodontitis completed a Sino-Nasal Outcome Test 22 (SNOT-22) questionnaire with incorporated additional symptom "malodor" before treatment. Moreover, they were distributed according to computed tomography (CT) radiological criteria such as degree of periapical pathology, anatomical ratio between maxillary lateral teeth and sinus floor, sinus mucosal thickening, and ostiomeatal complex condition. The elimination of odontogenic cause was performed by extracting causative tooth. Questionnaire was filled again 2 weeks, 3 months, and 6 months after treatment. All data were analyzed to search the clear indications for sinus surgical treatment. Results: Of 96 patients, 74 (77.1%) patients had full resolution of symptoms after dental cause was eliminated. For other 22 (22.9%) patients, symptoms persisted and sinus surgical treatment was indicated. In recovered group, mean SNOT-22 score was different between all periods of measuring, while within nonrecovered group, small differences were seen only when compared to before treatment. No statistically significant correlation between radiological criteria and rhinosinusitis healing after tooth extraction was found ( P  > .05). Statistically significant correlation was found between the disappearance of malodor/SNOT-22 score reduction after elimination of dental cause and healing success ( P  < .005). Conclusions: Our study revealed that extraction of causative tooth is an effective treatment of chronic odontogenic rhinosinusitis caused by apical periodontitis. CT criteria are not valuable indicator for sinus surgery, but persistence of malodor after 2 weeks is the strongest indication for this type of treatment.